High-power single-cycle mid-infrared transients generated via intra-pulse difference-frequency mixing at 2 μm - Butler, T. P.; Gerz, D.; Hofer, C.; Xu, J.; Gaida, C.; Heuermann, T.; Gebhardt, M.; Vamos, L.; Schweinberger, W.; Gessner, J. A.; Siefke, T.; Heusinger, M.; et al. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
The development of high-power, ultrafast coherent light sources in the mid-infrared (MIR) spectral region is subject to intensive research, due to the promise of improving both time- and frequency-domain spectroscopic methods, in particular for background-free field-resolved spectroscopy (FRS) [1,2]. In FRS, the molecular vibrational response of a sample upon impulsive, resonant excitation is measured in the time domain, e.g., via electro-optic sampling (EOS). Recent efforts have identified frequency down-conversion via intra-pulse difference frequency generation (IPDFG) as a viable route for producing high-power, waveform-stable MIR pulses for FRS [2,3]. With 2-μm driving sources, broader bandwidths [4,5] and higher efficiencies [5] can be achieved compared to 1-μm and 1.5-μm, in part due to a wider variety of nonlinear crystals with a high nonlinearity. Here, we present IPDFG driven by a 2-μm, thulium-fibre chirped-pulse amplification (CPA) system. This source uniquely combines broad bandwidth (6-18 μm), high average power (0.5 W), waveform stability, and a high repetition rate (50 MHz). In addition, we demonstrate for the first time EOS of the MIR using a short, high-power 2-μm sampling pulse.
CRIS-Team Scopus Importer:2023-04-20